Determinants of stock market performance in Malaysia: interest rate, consumer price index, exchange rate and crude palm oil price / Mohamad Asyraf Isa - Isa, Mohamad Asyraf (Faculty of Business and Management, 2019)
The aim of this study is to investigate the relationship between interest rate, consumer price index, exchange rate and crude palm oil price towards stock market performance in Malaysia. The study used Single Linear Regression Model and Multiple Linear Regression Model in order to find the relationship between interest rate, consumer price index, exchange rate and crude palm oil price towards Malaysian stock market performance. Thus, the data of variable is collected in yearly from year 1987 until 2018. From the findings and results, it shows that interest rate has significant negative relationship towards Malaysian stock market performance. Meanwhile, the consumer price index has significant positive relationship towards Malaysian stock market performance. However, changes of exchange rate and crude palm oil price have no significant relationship on the changes of Malaysian stock market performance. These results enhance our understanding of the relationship between the interest rate, consumer price index, exchange rate and crude palm oil price towards Malaysian stock market performance and should be guideline for investor, policy maker and future researcher.